PENINGKATAN HASIL BELAJAR HEADING SEPAK BOLA SISWA SEKOLAH DASAR DENGAN PERMAINAN BOLTUNG (Department of Physical Education, Sport, Health and Recreation, 2014)
This study aims to improve the learning outcomes of soccer heading in grade 4. Themethod used is Boltung game. Results showed that pre-cycle mastery learning onstudents' motor domain of only 33.3% and 20.8% of cognitive domains. Once appliedthe method Boltung game in cycle 1, there was an increase in mastery learning studentsin the areas of motor to 70.8%, 70.8% cognitive, and affective criteria 2.2 withconsiderable value. Thus the cycle is done 2 to further enhance students' mastery learningwhile using the method with the results of the game Boltung motor completeness 87.5%,83.3% cognitive, and affective criteria increased to 3.1 with good value. Conclusions Thisstudy shows that the method Boltung games can improve learning outcomes soccerheading.